Shortly, Many Patients May Not Find Doctors To Treat In Iraq! - Abed, Alaa; Abdulwahid, Dhurgham; Abdul-Hassan, Basim (Karbala Journal of Medicine, 2022)
The current general situation of Iraqi doctors' satisfaction, as an associated factor with brain drain problem, has been started to be studied academically. Serious findings have been registered due to serious challenges face the doctors. These seem to have resulted in frustration and made half of them think of emigration outside Iraq; more seriously one third may take this step shortly. This may lead to real shortage in the health services supplied, in addition to the shortage in the infrastructure, training process, updating equipment and other requirements. Unless effective and efficient measures are taken soon, the country may end with a new crisis, which adds a more burden on the suffering health institution.